Consumption and indebtedness practices of urban adolescents in schools from Temuco - Barros B., Solange (2015)
The adolescence is a stage of psychosocial development that is influenced by economicpolitical, social and cultural contexts. They not only affect the formation of social identities, but also the subjectivity, consumption practices and indebtedness of adolescents. Although these issues have been of interest for marketing, they also hold a space for debate in the fields of economic, social and developmental psychology. This article describes the differences in consumption and indebtedness practices of urban adolescents in schools from Temuco, Region of La Araucania, Chile. Through a qualitative descriptive research design of multiple cases, focus groups were performed with 30 adolescents finding differences in consumption and borrowing practices. The results reported an emotional aspect involved in cases of successful and frustrated shopping, questioning previous studies that indicate deficits in the foresight and savings of these adolescents.